Comparison of Oral Hygiene Using Chlorhexidine Solution and Hexadol Solution Towards Prevention of Ventilator Associated Pneumonia in Patients with Mechanical Ventilators - Indriana Natalia; Achmad Fauzi (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: This study aimed to determine the effect oral hygiene using chlorhexidine solution and hexanol solution towards prevention of ventilator associated pneumonia in patients with mechanical ventilators. Design: This type of research is a quasi-experimental study with a Control Group Pretest-Posttest research design Methods: The data used in this study are primary data with data collection techniques using the observation sheet. Test the hypothesis using the Independent T-Test method Results: The results showed that there was no significant difference between oral hygiene using Chlorhexidine and Hexadol in the prevention of VAP in Bekasi District Hospital with p value = 0.933 (p value > alpha 0.05). Conclusions : It can be concluded that there is no difference in oral hygiene using chlorhxidine and hexadol on the prevention of VAP. Future study should conducted similar study using more rigors methods and large sample.